Cold Micro Metal Forming Research Report of the Collaborative Research Center "Micro Cold Forming" (SFB 747), Bremen, Germany - Vollertsen, Frank; Friedrich, Sybille; Kuhfuß, Bernd; Maaß, Peter; Thomy, Claus; Zoch, Hans-Werner (Lecture Notes in Production Engineering,, 2020)
This open access book contains the research report of the Collaborative Research Center "Micro Cold Forming" (SFB 747) of the University of Bremen, Germany. The topical research focus lies on new methods and processes for a mastered mass production of micro parts which are smaller than 1mm (by forming in batch size higher than one million). The target audience primarily comprises research experts and practitioners in production engineering, but the book may also be of interest to graduate students alike.